2018
DOI: 10.1177/2150135118799041
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Effect of Ketorolac in Children After Congenital Cardiac Surgery

Abstract: Background: Ketorolac is used for pediatric analgesia after surgery despite its known platelet inhibition via the arachidonic acid (AA) pathway. The degree of platelet inhibitory effect after cardiac surgery is not well characterized. Thromboelastography with platelet mapping (TEG-PM) is emerging as a frequently used test to evaluate platelet inhibition via the AA pathway. Methods: Post hoc analysis of a data set collected in a prospective observational cohort study evaluating platelet inhibition in children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…87 High Strong While NSAIDs may not be associated with clinical bleeding in patients without other risk factors, they may impact platelet function and research is needed to better understand the impact of NSAIDmediated platelet inhibition in children. 73,75,88 Moderate Weak…”
Section: Moderate Weakmentioning
confidence: 99%
See 1 more Smart Citation
“…87 High Strong While NSAIDs may not be associated with clinical bleeding in patients without other risk factors, they may impact platelet function and research is needed to better understand the impact of NSAIDmediated platelet inhibition in children. 73,75,88 Moderate Weak…”
Section: Moderate Weakmentioning
confidence: 99%
“…92 Additionally, studies examining the risk of bleeding and changes to platelet function while receiving NSAIDs have found platelet function is altered but there is no increase in clinically significant bleeding. [73][74][75][76]79,88 It is unclear what the implication of changed platelet function is, and this warrants further research, particularly considering the additional risk factors in this population including cardiopulmonary bypass, presence of chest tubes, and surgical wounds.…”
Section: N/a Weakmentioning
confidence: 99%
“…There were seven retrospective cohort studies; two prospective PD studies; two retrospective case-control studies; two prospective, randomised studies; and one post hoc analysis of a prospective observational cohort study. [80][81][82][83][84][85][86][87][88][89][90][91][92][93] Medications included in these studies were opioids (morphine [43%], fentanyl [29%], hydromorphone [7%], remifentanil [7%]), and non-steroidal anti-inflammatory drugs (ketorolac [36%], acetaminophen [7%]).…”
Section: Analgesicsmentioning
confidence: 99%
“…Multiple studies found no increase in adverse renal or haematologic events except when ketorolac was administered in conjunction with aspirin, even in children <6 months old, although there was evidence of platelet dysfunction. [88][89][90][91][92] In addition to pain control, acetaminophen may be protective against acute kidney injury. 93…”
Section: Analgesicsmentioning
confidence: 99%
“…The Society for Pediatric Anesthesia recommends that ketorolac be considered as an adjunct to opioids in pediatric pain control, and data support its potential opioid-sparing effects in noncardiac surgery postoperative pediatric patients (17). In neonates, there is concern for acute renal dysfunction, necrotizing enterocolitis, and an increased risk of bleeding (18)(19)(20)(21)(22)(23)(24)(25)(26). Additionally, there are limited data on the use of ketorolac in neonates postcardiac surgery employing validated standardized definitions of renal impairment and bleeding.…”
mentioning
confidence: 99%